Development and on-farm validation of location specific IPM technology for rainy season cauliflower (Brassica oleracea var botrytis subvar cauliflora) - AHUJA, D B; SINGH, SWAROOP; SHARMA, PRATIBHA; MALIK, MEENAKSHI; SINGH, R V; KALRA, BHARTI (The Indian Journal of Agricultural Sciences, 2013)
IPM module comprising ecofriendly management practices such as soil solarization of nursery beds for 15-20 days, soil application of T. harzianum @ 2.50 kg/ha through FYM fortification, neem cake @ 50 g/m2, seed treatment with T. harzianum @ 4g/kg seed and imidacloprid 70 WS @ 3 g/kg seed, raised bed (15–25 cm) sowing (nursery stage), seedling dip in T. harzianum @ 4 g/l and imidacloprid 17.5 SL @ 0.5 ml/l of water, Chinese cabbage as a trap crop and planting of seedlings on ridges of 15–25 cm height (at the time of transplanting) and monitoring of population of S. litura through sex pheromone traps (5/ha), hand picking of larvae and egg masses of S. litura , plucking of pest infested leaves, need based application of SI NPV (250 LE/ha), neem oil 10%, novaluron 10 EC (250 ml/ha), spinosad 48 SC (75 g a.i/ha), and Mancozeb 64% + Metalaxyl 8% l @ 2g/l (after transplanting) was developed during rainy season of 2006 and 2007. It was evaluated in farmer’s participatory mode during rainy season of 2008 and 2009 with the objective to provide alternatives to synthetic pesticides and propose solution to the threat of environmental degradation. Implementation of Integrated Pest Management programme in irrigated cauliflower (Brassica oleracea L var botrytis subvar cauliflora) crop led to reduction in number of pesticide sprays of 50-60 percent and their replacement with safer pesticides. Lower insect and disease incidence with higher curd production was observed in the IPM fields as compared to conventional farmers practice fields. IPM module was able to cut the cost of crop protection resulting in higher benefit-cost ratio